2011
DOI: 10.1038/cddis.2011.56
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of autophagy is a potential modality for tumors refractory to radiotherapy

Abstract: Radiotherapy is a well-established treatment for cancer. However, the existence of radioresistant cells is one of the major obstacles in radiotherapy. In order to understand the mechanism of cellular radioresistance and develop more effective radiotherapy, we have established clinically relevant radioresistant (CRR) cell lines, which continue to proliferate under daily exposure to 2 Gray (Gy) of X-rays for >30 days. X-ray irradiation significantly induced autophagic cells in parental cells, which was exiguous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 39 publications
4
61
1
1
Order By: Relevance
“…1B; P<0.01). The differentiated TAM group demonstrated the highest expression levels of CD68, CD204 and CD206 cell surface markers among the 3 groups, consistent with previous studies (15)(16)(17) (Fig. 1C).…”
Section: Induction Of Thp-1 Differentiation and The Identification Ofsupporting
confidence: 91%
See 1 more Smart Citation
“…1B; P<0.01). The differentiated TAM group demonstrated the highest expression levels of CD68, CD204 and CD206 cell surface markers among the 3 groups, consistent with previous studies (15)(16)(17) (Fig. 1C).…”
Section: Induction Of Thp-1 Differentiation and The Identification Ofsupporting
confidence: 91%
“…Studies have also confirmed that TAMs secrete TGF-β, PDGF, tumor necrosis factor-α, matrix metalloproteinase-9 and other factors, to promote tumor angiogenesis and accelerate tumor growth (21,24). Previous studies have demonstrated that TAMs secrete PDGF, IL-1 and -6 to aid tumor cell survival and reduce tumor radiosensitivity (15,16,25). Thus, the study of TAMs may uncover novel methods to improve the results of radiotherapy.…”
Section: Discussionmentioning
confidence: 88%
“…298 As we identify new drugs for modulating autophagy in clinical applications, this type of information may prove useful in the identification of subgroups of patients for targeted therapy. [299][300][301] In mouse and rat tissues, endogenous LC3, ATG4B, and ATG9A have been detected by immnohistochemical analyses using both paraffin sections and cryosections. 208,[302][303][304] When autophagosomes are absent, the localization pattern of LC3 in the cells of various tissues is diffuse and cytosolic.…”
mentioning
confidence: 99%
“…mTOR plays a critical role in tumor development, invasion, and metastasis, acting as a signal integrator that modulates permissive signals from various pathways and a diversity of growth-promoting processes (5). The mTOR inhibitor rapamycin and its analogs have been shown to induce autophagy, which somewhat paradoxically is associated with its radiosensitizing effects (6)(7)(8). The mechanisms by which autophagy can mediate both radiation resistance and radiosensitivity when radiation and mTOR inhibitor are combined remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%